The Relationship of Gargling Activity to The Amount Growth of Candida sp Fungus in Saliva In People With Type 2 Diabetes Melitus - Azahra, Sresta; Rayhana, Annisa; Anggrieni, Nurul (UPPM Poltekkes Kemenkes Ternate, 2024)
Diabetes mellitus (DM) is a disease caused by abnormalities in the insulin hormone which can not work to control glucose properly. DM is a predisposing factor for oral candidiasis because salivary secretions containing excess sugar will support the growth of Candida sp. Oral candidiasis can be anticipated by gargling with commercial mouthwash. The research aimed to determine the relationship between gargling activity and the amount of Candida sp fungus growth in the saliva of DM sufferers. This type of research is pre-experimental with a one-group pretest-posttest design. The total was 30 saliva samples from DM sufferers at the Sidomulyo Samarinda Health Center using a purposive sampling technique. Data were analyzed univariately and bivariately. The research results showed that the presence of Candida sp fungus in DM sufferers based on age in the elderly category (>40 years) was 24 (88.8%); wo25 (89.2%). Growth of Candida sp fungus before gargling 27 (90%) were positive for Candida sp fungus; after gargling, 15 (50%) were positive for Candida sp. The number of Candida sp fungus growth based on activity before gargling was 27 (90%) with the number of Candida sp colonies <400 CFU/ml; after gargling 30 (100%) with the number of Candida sp colonies <400 CFU/ml. The statistical test results obtained a significant value of 0.000 < 0.05, it can be concluded that there is a relationship between mouth gargling activity and the amount of Candida sp fungus growth in the saliva of DM sufferers.